Coordination Failure in Technological Progress, Economic Growth and Volatility - Mei Li (Queen's University, Department of Economics, 2007)
Technological progress has long been posited to be crucial in a country's economic growth. This paper argues that coordination failure in a country's new technology investment can be one of the barriers in a country's capital accumulation and economic growth. The global game established by Morris and Shin(2000) is extended to a two-sector overlapping generations model where capital goods can be produced by two different technologies. The first is a conventional technology with constant returns, which are perfectly revealed to economic agents. The second is a new technology exhibiting increasing return to scale due to technological externalities, whose returns economic agents only have incomplete information about. Economic agents have to choose which technology to invest in. My model reveals that under certain circumstances coordination failure in the capital goods sector will occur and be manifested as under-investment in the new technology. In this way, I explain how coordination failure in a country's technology updating process leads to slower capital accumulation and economic growth. More interestingly, the model generates a positive correlation between economic growth and volatility through a new channel associated with coordination failure. Policy implications are discussed as well.
Keywords: D82; D9; 330; Economic Growth; Technological externalities; Coordination Failure; Wirtschaftswachstum; Technischer Fortschritt; Investition; Unvollkommene Information; Entscheidung unter Unsicherheit; Koordination; Overlapping Generations; Theorie